Anti-Interleukin-22-Neutralizing Antibody Attenuates Angiotensin II-Induced Cardiac Hypertrophy in Mice - Ye, Jing; Liu, Ling; Ji, Qingwei; Huang, Ying; Shi, Ying; Shi, Lei; Liu, Jianfang; Wang, Menglong; Xu, Yao; Jiang, Huimin; Wang, Zhen; Lin, Yingzhong; et al. (Mediators of Inflammation, 2017)
Background. Interleukin- (IL-) 22 is considered a proinflammatory cytokine. Recent evidence has demonstrated that it plays a role in cardiovascular diseases. In the recent study, we investigate whether IL-22 is involved in cardiac hypertrophy. Methods. Angiotensin II was used to build hypertrophy model and the IL-22 and IL-22 receptor 1 (IL-22R1) levels in heart tissue were measured. In addition, angiotensin II-treated mice received an injection of anti-IL-22-neutralizing antibody (nAb) to investigate the effects of IL-22 nAb on myocardial hypertrophy, cardiac function, and cardiac fibrosis; the activation of the signaling pathway and the prohypertrophic inflammatory cytokine mRNA levels was detected. Furthermore, the effect of IL-22 nAb on angiotensin II-induced hypertrophy in vitro was also determined. Results. IL-22 and IL-22R1 levels were significantly increased after angiotensin II infusion. Anti-IL-22 nAb significantly alleviated the severity of hypertrophy, prevented systolic and diastolic abnormalities, reduced cardiac fibrosis, STAT3 and ERK phosphorylation, and downregulated the mRNA expression of IL-17, IL-6, IL-1β, IFN-γ, and TNF-α. In addition, IL-22 nAb attenuated angiotensin II-induced hypertrophy in H9C2 cells. Conclusion. Our data demonstrated that neutralization of IL-22 alleviated angiotensin II-induced cardiac hypertrophy. The downregulation of IL-22 may be a novel therapeutic strategy to prevent cardiac hypertrophy.